Field evaluation of the effects of air convection in energy harvesting asphalt pavements - Chiarelli, A.; Dawson, Andrew; Garcia, Alvaro (Elsevier, 2017)
In this article, the performance of a convection-powered air flow through an asphalt prototype pavement is investigated in a field test. An asphalt prototype pavement with pipes buried in its aggregate layer was connected to a constant temperature heat source and installed at the University of Nottingham, UK. In the experimental configuration chosen, air at 15 °C was free to flow through the prototype pavement by natural convection and exit through a vertical chimney. The natural convection flow was meant to cool down or heat up the pavement based on the temperature gradient between the pavement surface and the air in the pipes. The experimental setup included a weather station and aimed to analyse the effect of the heat fluxes from and to the air in the pipes on the development of the surface temperature.